Democratic Republic of Congo’s agrifood system structure and drivers of transformation - Diao, Xinshen; Randriamamonjy, Josee; Thurlow, James; Ulimwengu, John M.; Ellis, Mia (International Food Policy Research Institute, 2023)
Agriculture in the Democratic Republic of Congo (DRC) is dominated by subsistence farming. Households grow food mainly for their own consumption and sell only when they have a surplus. The main crops are cassava, maize, yams, plantains, and rice (FAO 2019). Commercial farming of cash crops such as coffee, palm oil, rubber, and sugar is done on a smaller scale. With constant political instability, infrastructure deficiencies, and lack of investment in DRC, the expansion and productivity of commercial farming have been constrained (World Bank 2020). Livestock and fisheries are also important agrifood subsectors and face constraints similar to the crop subsectors. Despite these challenges, DRC possesses robust agricultural potential due to its vast arable land resources, abundant water resources, and its diverse climatic conditions, which are suitable for a wide variety of crops. There is also potential for further development of the fisheries sector due to the country’s extensive river system and large lakes. In this brief, we look beyond primary agriculture to understand the recent performance of DRC’s broader agrifood system (AFS) and how it is contributing to growth and transformation in the country.